LITERASI PARIWISATA MASYARAKAT KECAMATAN BAROKO KABUPATEN ENREKANG - Harifuddin, Harifuddin; Iskandar, Abdul Malik; Zainuddin, Rasyidah (Arunika: Jurnal Pengabdian Masyarakat, 2022)
Community empowerment becomes effective when the community responds to the activities carried out in empowerment. This service activity is a form of community empowerment in the tourism sector with a series of socialization, training, and mentoring activities. The targets of this empowerment are community groups such as youth organizations, tourism awareness groups, and tourism observer groups whose members come from the local community. This activity started with a half day FGD to identify their needs. Based on FGD data, the results of the analysis show that the community needs socialization about tourism perspectives, training is needed related to tourism potential mapping, tourism object management, supporting facilities and infrastructure management and guest management. To strengthen the training, the community also needs assistance from professionals and professional institutions such as professional guides under the Indonesian Tour Guide Association (HPI), Tourism Village Association (ASIDEWI), Indonesian Archipelago Tourism Village (DEWISNU) regarding the management of local tourism potential. In the implementation of socialization, the community was presented with material about the urgency of tourism to improve their economy. The Alla Village community has all of these potentials, both natural potential, cultural potential, and garden potential. All require management by skilled, knowledgeable and professional local people. The training activity was continued with mapping and identifying tourism potential and found many locations that could be managed professionally. This PKM recommends advanced training to explore more deeply the local potential and the potential of local human resources.